Protective Effect of the Aqueous Extract of Cyamopsis tetragonoloba Seed against the Paracetamol-induced Toxicity in Female Wistar Albino Rats - Simon, Jerine Peter; Namachivayam, Arunraj; Katturajan, RamKumar; Nithiyanandam, Sangeetha; Parthasarathy, Manisha; Sabina, Evan Prince (Indian Journal of Pharmaceutical Education and Research, 2022)
Background: Paracetamol is also known as acetaminophen which is the most widely and commonly used painkiller drug among the overall human population. On excess usage and high dosage, paracetamol can cause liver injury, gastrointestinal damage and kidney damage. Cyamopsis tetragonoloba is the most commonly available plant in India which has weight loss properties as well as used to treat cancer and diabetes. Aim: This study is to estimate the potential effect of C. tetragonoloba against paracetamol-induced hepatotoxicity. Methodology: There were seven groups of rats which were divided as follows:Group-1 as Normal control, Group-2 administrated with paracetamol (900mg/kg b.w./day, i.p.), Group-3 is induced with paracetamol (900mg/kg b.w./day, i.p.) and C. tetragonoloba (500 mg/kg b.w./day, p.o.), Group-4 is same as Group-3 however C. tetragonoloba dosage differs as 1000 mg/kg b.w./ day, p.o.,Group-5 is given with paracetamol (900 mg/kg b.w./day, i.p.) and silymarin (25 mg/kg b.w./day, p.o.), Group-6and Group-7 is administrated with C. tetragonoloba (500 mg/kg b.w./day, p.o.) and C. tetragonoloba (1000 mg/kg b.w./day, p.o.) respectively. After 4 hrs of drug administration, the animals were sacrificed from which blood and organs were collected for the toxicity study. The samples were used for the analysis of liver and kidney enzyme markers, antioxidant assays and histopathological changes. Conclusion: The study has proven that C. tetragonoloba has a potential effect on the toxicity-induced groups. On compared to the standard drugs, C. tetragonoloba has shown better results.
Keywords: Cyamopsis tetragonoloba; Pharmaceutical drug-induced toxicity; Plant; extract; Paracetamol; Wistar albino rats